Convolutional Neural Network Committees for Handwritten Character Classification - Ciresan, D. C.; Meier, U.; Gambardella, L. M.; Schmidhuber, J. (2011 International Conference on Document Analysis and Recognition, 2011)
In 2010, after many years of stagnation, the MNIST handwriting recognition benchmark record dropped from 0.40% error rate to 0.35%. Here we report 0.27% for a committee of seven deep CNNs trained on graphics cards, narrowing the gap to human performance. We also apply the same architecture to NIST SD 19, a more challenging dataset including lower and upper case letters. A committee of seven CNNs obtains the best results published so far for both NIST digits and NIST letters. The robustness of our method is verified by analyzing 78125 different 7-net committees.